Analisis Pengaruh Produk, Harga, dan Pelayanan Terhadap Keputusan Nasabah Menggunakan Produk pada PT. Asuransi Jiwasraya (Persero) Cabang Palu - Ishak, Aditya P (Universitas Sam Ratulangi, 2019)
The study aims to determine the effect of products, prices, and services on purchasing decisions at PT. Jiwasraya Insurance (Persero) Palu Branch. Type of associative research using multiple linear regression analysis techniques. The test results show that the effect of products, prices, and services together using the product has a significant and positive effect on customer purchasing decisions at PT. Jiwasraya Insurance (Persero) Palu Branch. Management of PT. Asuransi Jiwasraya (Persero) Palu Branch should give more attention to products, prices, and services. Because this can encourage people to use products at PT. Jiwasraya Insurance (Persero) Palu BranchKeywords: Products, Prices, Services, Customer Decisions